Dampak Perubahan Transportasi Air Ke Darat Pada Masyarakat Kecamatan Banjarmasin Selatan Tahun 1990-2008 - Muhammad Sofian Syauri; Mansyur; Mohamad Zaenal Arifin Anis (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The main problem studied in this research concerns the impact of changing water transportation to land transportation in the South Banjarmasin sub-district 1990-2008. There is negative impact, namely land transportation pollution. general, the definition of air pollution is the difference in actual air composition with normal air conditions where the actual air composition does not support human life. Air pollution materials or substances themselves can be in the form of gases and particles. Then there was conflict over land acquisition in the context of road construction. The amount of land compensation demanded by community because their land was affected by a road construction project was not in accordance with the budget owned the Banjarmasin City Government. Apart from that, individuals usually play for their own interests in order to gain profits. The positive impact on the people of South Banjarmasin District resulting from land transportation general overcoming distance and communication gap in transportation, in this case it necessary to overcome the distance and communication gap between the place of origin and the destination. Furthermore, speeding up the traffic of people and goods. The method used in this research uses the historical method through the Heuristic stage (data collection), internal and external criticism of the data obtained, interpretation and historiography of historical writing based on the data that has been obtained according the researcher's objectives. The novelty of this research that no previous research has specifically discussed the impact of changes in water transportation, especially in the South Banjarmasin sub-district area.